2008
DOI: 10.2174/1874226200801010013
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Reactive Anti-Avian H5N1 Influenza Neutralizing Antibodies in a Normal ‘Exposure-Naive’ Australian Blood Donor Population

Abstract: Abstract:It is necessary to understand whether some humans possess natural humoral-immune protection for avian-H5N1 influenza. To broadly assess an exposure naïve cohort we have examined intravenous immunoglobulins (IVIGs) isolated from pools of many thousands of normal Australian blood donations. In studies of the anti-H5N1 antibody potential of these highly purified IVIG therapeutics and of individual donor sera we have identified antibodies that bind to both H5N1 surface envelope and internal viral proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 17 publications
4
21
0
Order By: Relevance
“…Additionally, seasonal vaccination has been shown to elicit these antibodies [48] as well as primary infection in children [49]. As demonstrated by a precedent study where cross-reactive anti-avian H5N1 influenza neutralizing antibodies were found in normal “exposure-naïve” Australian blood donors [50], it is highly unlikely that the individuals sampled in this study had ever come into contact with HPAI H5 or H7 viruses or indeed antigenically related LPAI H5 or H7 viruses. Therefore, it is postulated that this highly sensitive neutralization assay is measuring broadly specific antistalk antibodies that have been elicited via exposure to H1 and H3 viruses and/or antibodies that recognize highly conserved sequences located underneath the RBS of individual subtypes (especially H1N1, H3N2, and H5N1) [51].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, seasonal vaccination has been shown to elicit these antibodies [48] as well as primary infection in children [49]. As demonstrated by a precedent study where cross-reactive anti-avian H5N1 influenza neutralizing antibodies were found in normal “exposure-naïve” Australian blood donors [50], it is highly unlikely that the individuals sampled in this study had ever come into contact with HPAI H5 or H7 viruses or indeed antigenically related LPAI H5 or H7 viruses. Therefore, it is postulated that this highly sensitive neutralization assay is measuring broadly specific antistalk antibodies that have been elicited via exposure to H1 and H3 viruses and/or antibodies that recognize highly conserved sequences located underneath the RBS of individual subtypes (especially H1N1, H3N2, and H5N1) [51].…”
Section: Discussionmentioning
confidence: 99%
“…To permit removal from the AAHL secure area and to allow the virus to be handled safely for antibody binding and protein analyses the viruses were inactivated by exposure to 5 megarads of radiation. The purity of the viruses was accessed by their SDS-PAGE profiles (see below and Lynch et al, 2008). …”
Section: Methodsmentioning
confidence: 99%
“…We earlier investigated whether Australian blood donors – uniquely geographically separated from the rest of the world on an island continent and naive to H5N1 exposure – may contain heterosubtypic antibodies, which cross-react with H5N1. Indeed, we provided evidence for heterosubtypic antibodies that bound to many of the proteins of H5N1, including both surface as well as internal proteins (Lynch et al, 2008). …”
Section: Introductionmentioning
confidence: 96%
“…As seasonal antibodies provide the main correlate of homotypic neutralizing protection against influenza (Schild et al, 1975; Virelizier, 1975; Delem and Jovanovic, 1978; Kashyap et al, 2008), we now raise the question of whether seasoned, cross-reactive antibodies similarly provide a significant contribution for heterosubtypic protection. Certainly, our own findings implicate a pre-existing pool of anti-influenza antibodies in an unexposed Australian population that can protect against avian H5N1 influenza, in vitro , along with H5-hemagglutinin binding antibodies that are most prominent with adult age (Lynch et al, 2008; Stelzer-Braid et al, 2008). This is also supported by observations of cross-reactive anti-neuraminidase antibodies from unexposed humans that partially protect H5N1 infected mice (Sandbulte et al, 2007).…”
Section: Introductionmentioning
confidence: 73%
“…Shown is an overview of the respective mechanisms, the proteins they target, evidence of their cross-protective power, and avenues for the development of heterosubtypic-based vaccine and antiviral interventions for broad based influenza protection. [References: Jameson et al, 1999; Tumpey et al, 2001; Kong et al, 2006; Luke et al, 2006; Ichinohe et al, 2007; Roy et al, 2007; Sandlbute et al, 2007; Simmons et al, 2007; Zhou et al, 2007; Carragher et al, 2008; Gioia et al, 2008; Kayshap et al, 2008; Kreitz et al, 2008; Lee et al, 2008; Lynch et al, 2008; Roti et al, 2008; Stelzer-Braid et al, 2008]…”
Section: Introductionmentioning
confidence: 99%